2017
DOI: 10.18632/oncotarget.23029
|View full text |Cite
|
Sign up to set email alerts
|

Cell properties of nucleus pulposus progenitor cells declines with intervertebral disc degeneration

Abstract: Endogenous repair of nucleus pulposus progenitor cells (NPPCs) has exhibited encouraging regenerative potential for treating intervertebral disc degeneration (IDD). However, few studies have explored the properties of NPPCs during the progression of IDD. Hence, additional studies are needed to characterize NPPCs from human degenerated intervertebral disc (IVDs) at different Pfirrmann grades. In this study, human NPPCs were isolated and identified from human IVDs with different Pfirrmann grades. Then, cell biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Noteworthily, the number of CFUs was found to be correlated with Pfirrmann grading scheme of disk degeneration in human NPPC. 16,24 The Tie2 immune staining of 3D pellet culture (Fig. 8) was expected to stain specifically the membranes as it is a surface marker also known as CD202b.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthily, the number of CFUs was found to be correlated with Pfirrmann grading scheme of disk degeneration in human NPPC. 16,24 The Tie2 immune staining of 3D pellet culture (Fig. 8) was expected to stain specifically the membranes as it is a surface marker also known as CD202b.…”
Section: Limitationsmentioning
confidence: 99%
“…[21][22][23] Recently, it was reported that the ability to form colonies of isolated NPPCs from human surgical samples is dependent on Pfirrmann grading of the disk. 24,25 Despite their early fading, the study of this marginal subpopulation within the NP might give rise to a better understanding of how these cells affect IVD health, and what conditions are required to maintain them longer. Moreover, a deeper understanding might lead to new approaches for regeneration of the IVD.…”
mentioning
confidence: 99%